Evolving adoptive cellular therapies in urological malignancies. Issue 6 (June 2017) - Wong, Yien Ning Sophia; Joshi, Kroopa; Pule, Martin; Peggs, Karl S; Swanton, Charles; Quezada, Sergio A; Linch, Mark
Summary: Immunotherapies have long been used to treat urological cancers but rarely lead to cure. In the past 5 years, success of immune checkpoint inhibition has led to a resurgence of enthusiasm for immunotherapy in the treatment of solid tumours. Increased understanding of tumour immune biology, technological advancements of gene transfer and cell culture, and improved clinical infrastructures for routine delivery of cell products, has made cell-based immunotherapeutics a real prospect for cancer therapy. These scientific and clinical activities, attempting to exploit the innate and adaptive immune systems for therapeutic gain, are well exemplified by the urological malignancies of renal, bladder, prostate, and penile cancer, a group of anatomically localised diseases, each with a distinct biology and different immunotherapeutic challenges. In this Review, we present the results of clinical studies investigating autologous cellular therapies in urological malignancies. Specifically, we discuss the rationale for upcoming studies, and how novel therapies and adoptive cell combinations can be used for personalised cancer therapy.